2012
DOI: 10.1002/aenm.201200679
|View full text |Cite
|
Sign up to set email alerts
|

Toward High‐Performance Semi‐Transparent Polymer Solar Cells: Optimization of Ultra‐Thin Light Absorbing Layer and Transparent Cathode Architecture

Abstract: Organic photovoltaics (OPVs) have recently attracted extensive interest due to their potential for low cost, high throughput manufacturing to solve the scalability problem in solar energy. A typical OPV is based on the bulk-heterojunction (BHJ) device confi guration, which sandwiches a layer of polymer donor and fullerene acceptor blend between a transparent electrode (such as indium tin oxide (ITO)) and an opaque, refl ective metal electrode. These devices have shown high power conversion efficiencies (PCE) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 35 publications
0
115
1
Order By: Relevance
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…There are several organic-based approaches that produce semi-transparent OPV devices that exhibit good electrical performance (Figure 8), whereby they are composed of organic electronic materials, and transparent electrodes based on a wide range of different materials, including conducting polymers [122][123][124][125], thin metal films [126], sputtered transparent conducting oxides of LiCoO2/Al [127], carbon nanotubes [122], graphene [128], and silver nanowires (Ag NWs) [129][130][131][132][133]. Recently, a study by Beiley et al [134], has shown the development of a semi-transparent OPV which consists of a silver nanowire (Ag NW) and zinc oxide nanoparticle (ZnO NP) composite top electrode, and has a power conversion efficiency of 5.0%.…”
Section: Organic Photovoltaics (Opvs)mentioning
confidence: 99%
“…First, we will consider what is, perhaps, the most straightforward approach consisting of further decreasing the polymer band gap to obtain a larger transparency in the visible spectrum. [79][80][81] One of the most relevant features of this approach is that it provides a very nice colorless high level of transparency. On the other hand, the limited harvesting at all wavelengths resulting from the low reflectivity of the top electrode can be partially compensated with the incorporation of an additional absorber layer in a tandem configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] For example,i nterlayers located between the active layer and conductive electrodes improve the selectivity of charge transport, and minimize series resistance (R s ), leading to PCE values exceeding 9% for single junction PSCs. [3][4][5][6][7] A blend of poly(ethylenedioxythiophene)a nd poly(styrene sulfonate) (PEDOT:PSS) functions as as olution-processible hole-selective anode modification layer that has proven generally useful for PSCs.R ecent efforts have been devoted to developing new cathode modification layers to enhance electron extraction efficiency.S mall-molecule organic interlayers integrated into PSCs afford noteworthy device improvement, including functional fullerenes, [4,[8][9][10][11][12][13][14][15][16] perylene diimides, [17] and oligomeric fluorenes. [5] Polymer interlayers provide advantages of both facile solution processing and robust film formation, with two recently reported examples being poly(ethyleneimine) (PEI) [18,19] and tertiary-aminesubstituted polyfluorene (PFN).…”
Section: Polymersolarcells(pscs)provideanavenuetoinexpensivementioning
confidence: 99%